1976
DOI: 10.1139/v76-175
|View full text |Cite
|
Sign up to set email alerts
|

The structure and equilibria of a manganese(II) complex of fulvic acid studied by ion exchange and nuclear magnetic resonance

Abstract: The binding of Mn2+ to a well characterized fulvic acid sample is reported based on the competition with K+ in an ion exchange equilibration. The free energy of binding of [Formula: see text] to fulvic acid is only 1–2 kJ/equivalent more favourable than that for K+. This suggests an outer sphere electrostatic structure for the complex. The suggestion is confirmed by observation of minimal change in the presence of fulvic acid of the effect of paramagnetic Mn2+ on the nmr spectra of water. The interpretation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

1976
1976
2010
2010

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(13 citation statements)
references
References 13 publications
(18 reference statements)
2
10
0
1
Order By: Relevance
“…This interpretation contrasts with the common assumption that bonding of metals to organic matter is a chelation or complexation reaction with more than one functional group. Spectroscopic evidence reveals that some metals (e.g., Mn 2 +) do not form inner-sphere complexes with organic matter (Alberts et al, 1976;Gamble et al, 1976;Deczky and Langford, 1978;McBride, 1978b). In fact, Cu 2 +-humic acid complexes at fairly high-Cu 2 + sorption levels are not particularly stable relative to Cu 2 + ch elates (see Figure 17) but comparable in stability to Cu-acetate.…”
Section: Metal Adsorption By Organic Mattermentioning
confidence: 99%
“…This interpretation contrasts with the common assumption that bonding of metals to organic matter is a chelation or complexation reaction with more than one functional group. Spectroscopic evidence reveals that some metals (e.g., Mn 2 +) do not form inner-sphere complexes with organic matter (Alberts et al, 1976;Gamble et al, 1976;Deczky and Langford, 1978;McBride, 1978b). In fact, Cu 2 +-humic acid complexes at fairly high-Cu 2 + sorption levels are not particularly stable relative to Cu 2 + ch elates (see Figure 17) but comparable in stability to Cu-acetate.…”
Section: Metal Adsorption By Organic Mattermentioning
confidence: 99%
“…The iron dependence is first power. binding of ligands at Fe(I1I) shortens the electronic relaxation times and alters nmr broadening (6). Nuclear magnetic resonance did not provide a probe of the number of water molecules remaining coordinated.…”
Section: (6) Bincling Eqzrilibri~rm and Natural Watermentioning
confidence: 96%
“…Manganese(II) forms complexes in soil solution with organic substances such as organic acids, amino acids, and humic acids. Nuclear magnetic resonance spectroscopy (NMRS) analysis showed that Mn 2þ bound to fulvic acid remains fully hydrated, indicating that the complex formed between humates and Mn 2þ can be described as an outer-sphere complex wherein the ligand does not interact directly with the Mn electrons [20]. Therefore, Mn-organic ligand complexes may be still quite labile and available to plants and microorganisms.…”
Section: Solution and Solid Formsmentioning
confidence: 99%